Mixed-ligand diruthenium complexes: theoretical modelling and interpretation of electronic absorption spectra - Mutomb, Jean-Luc (Department of Chemistry, 2026)
The speciation and improved solubility of Ru₂(μ-O₂CCH₃)₃(μ-2-Fap)X complexes, where 2-Fap is 2-(2-fluoroanilino)pyridinate, and X represents Cl, Br or I, are influenced by the axial ligand (X) lability and solvent coordination at the axial site. These complexes have Ru(II) and Ru(III) metal centers that can be written as Ru₂⁵⁺. Researchers have observed distinctive spectroscopic and electrochemical characteristics of these Ru₂⁵⁺ complexes but lack an established theoretical framework to fully understand specific characteristic traits, such as a shoulder band in the visible range of the ultraviolet-visible (UV-Vis) spectrum in aqueous solutions, the absence thereof in solutions containing excess chloride ions, as well as the solvatochromic shifts of the UV-Vis bands in aqueous and non-aqueous solvents. This study therefore investigates the characteristics of Ru₂(μ-O₂CCH₃)₃(μ-2-Fap)X complexes using time-dependent density functional theory (TD-DFT) calculations that utilize the PBE/LANL2DZ level of theory and an Integral Equation Formalism Polarizable Continuum (IEF-PCM) solvent model using water, DCM and DMSO. Calculation of natural transition orbitals (NTOs) and spectrum deconvolution methods have aided in characterizing the electronic transitions of the prominent UV band at 250-350 nm as a combination of δ(Ru₂) → π*(Np,C), π(Cl) → π*(Cp,Np) and π(Cl) → π*(Cₐ) transitions, where the subscript “a” and “p” represents the aniline and pyridine moieties, respectively. On the other hand, the weak band at the 400-450 nm visible region is ascribed to the π (Cₐ,Nₐ)/δ*(Ru₂) → π*(Cp,Np) transition, whereas the broad band at 450-750 nm has been characterized as a combination of π(Cl,Ru₂) → δ*(Ru₂), δ(Ru₂) → δ*(Ru₂), π(Cl,Ru₂) → π*(Ru₂), π(F,Cₐ-Cₐ) → π*(Ru₂), π(Cl) → π*(Ru₂) and π(Cl,F,Cₐ-Cₐ) → π*(Ru₂) transitions. The near-infrared (NIR) region is characterized by a weak band at 900-1000 nm, which mainly consists of a δ(Ru₂) → δ*(Ru₂) transition. The equilibria, involving the cationic, neutral and anionic species in solution and corresponding spectroscopic changes are interpreted for Ru₂(μ-O₂CCH₃)₃(μ-2-Fap)X, along with the solvatochromic shift.